Influence of Micro-Cavity Effect and Architecture in the Blue Phosphorescent Organic Light-Emitting Diodes. (1st January 2017) - Kou, Zhiqi; Ji, Changyan; Yang, Feiyu; Yang, Liping; Wang, Xiaoping
Abstract : The performance of the blue phosphorescent organic light-emitting diodes (PHOLEDs) can be affected by the range of the recombination zone (RZ) and the architecture in the emitting layer (EML). In order to change the width and location of RZ, a series of devices with the double emitting layers are fabricated. The range of RZ can be judged by the electroluminescence spectra around 500 nm due to micro-cavity effect of RZ. Then, another series of devices with a single host EML1 (mCP:FIrpic, x nm) and a mixed host EML2 (mCP:TPBi:FIrpic, y nm) are fabricated under the same total thickness of EML (x+y = 30 nm), when x is 15 nm, the maximum luminance and power efficiency can reach 9073 cd/m 2 (at 8 V) and 23.4 lm/W (at 10 3 cd/m 2 ), respectively. Both the driving voltage and efficiency roll-off are also improved.